Modern methods for evaluating strategic performance and its role in improving the efficiency and effectiveness of performance - Jarullah, Mahdi Abed; Jarullah, Mahdi Abed; Doaim, Sarmad Salman (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify modern methods of evaluating strategic performance in improving the efficiency and effectiveness of performance, and to identify if there are statistically significant differences between the variables (gender, academic rank, job title, number of years of experience), and the study sample consisted of(60) male and female employees Department heads, administrative directors and divisional directors ,The researcher used the questionnaire as a tool for the study, and the results of the study showed that modern methods of evaluating strategic performance in improving the efficiency and effectiveness of performance in private colleges came with a high degree from the point of view of the study sample. The results of the study also showed an apparent variation in the arithmetic means and standard deviations attributed to the variables (gender, academic rank, job title, number of years of experience) and in the fields of the tool as a whole. The study recommended the necessity of conducting training courses to develop performance and raise their skills and competencies to obtain distinguished quality in strategic performance in private colleges.